Pengaruh Pemberian Ankle Strategy Exercise Terhadap Keseimbangan Statis Pada Lanjut Usia - Sari, Fais Elmi, Agus Widodo, S.Fis, M.Kes (2016)
Background: Balance is the major component in maintaining the posture of the human body to be able to stand-up and maintain the position of the body. Musculoskeletal system has an important role in maintaining the balance of the human body. Less physical activity can cause static balance does not work optimally. The purpose of this study was to determine the effect of Ankle Strategy Exercise toward static balance in the elderly. Research Objective: Experimental research has been done by using pre-test and post-test design. The sample in this study were 31 elderly who live in Sidomulyo. Ankle Strategy Exercise therapy was given to the respondents for 3 times in 1 week. Functional reach test was used as a measurement instrument to check the static balance. It was done before treatment (0-session) and after treatment (18- session) on each subject. Research Methode: The test results obtained from the Kolmogorovsmirnov showed that the static balance data were normally distributed with a p-value more than 0.05 (p> 0.05). Based on the result of paired sample t-test on the group of pre-test and post test Ankle Strategy Exercise through FRT, obtained t value - 23,386 with significance (2-tailed) 0.000. Since the value of significance (2- tailed) is smaller than 0.05 (0.000 <0.05), then indicated that H0 is denied and H1 is accepted. Results: Based on the statistic result, it is concluded that the value of sig (2-tailed) is less than 0.05 (0.000 <0.05) means that there is a significant influence of the Ankle Strategy Exercise to increase the static balance.